Características dentoalveolares intra e interarcos da má oclusão de classe II subdivisão com vistas ao diagnóstico e planejamento do seu tratamento - Pereira, Alexandre Zilioli [UNESP] (2014)
Class II subdivision malocclusion has intra and interarch dentoalveolar morphological differences, consisting of a Class I asymmetric occlusal relationship on one side of the dental arch and Class II on the other side, and we can observe differences and similarities when compared to Class I and Class II malocclusions. The aim of this study was to evaluate those differences and similarities (dimensional and positioning intra and interarch tooth characteristics) through digital study models between patients with Class I, II and Class II subdivision. The sample consisted of 90 dental casts obtained from 3 adolescents groups with no prior orthodontic treatment, 30 obtained of Class I patients, 30 of Class II patients and 30 of Class II subdivision patients. These dental casts were scanned using the R500 3D Scanner and the 3D image will be used to analyze and compare the groups through the measure of interarch relationship, arch dimensions and space condition. The results showed that Class II subdivision presented in the lower bow a narrowed dental arch on the class I side and a wider dental arch on the class II side. Comparing the data of malocclusion, Class II division 1, showed a lower distance in the superior intermolar. For the canines and molars rotation measurements no rotation pattern was notice between the malocclusion, however, Class II subdivision presented a greater rotation of the first superior molar on the Class II side compared to the Class I side first molar. For the anteroposterior measures, Class II subdivision presented in the superior arch a lower distance on the left side compared to the right side, and in the inferior arch the opposite was observed. In conclusion, the main dental differences observed in the Class II subdivision related to Class I and Class II division 1 are of anteroposterior character, and also we could notice that in Class II ... (Complete abstract electronic access below)